Методы и средства анализа текстов публикаций для исследования деятельности научных школ - Шаховская, Н.Б.; Нога, Р.Ю. (Проблемы управления и информатики, 2015)
Проаналізовано методи опрацювання текстової інформації з багатьох розрізнених інформаційних ресурсів. Удосконалено метод екстракції даних з наукової публікації, а також метод кластеризації k-середніх для поділу наукових статей за науковими школами. Визначено метрику якості кластерного рішення. Апробовано розроблені методи для електронної бібліотеки та наукової установи. Thre are considered the methods of processing text information from a plurality of disparate information resources. The method of extraction of data from scientific publications is improved as well as the method of k-means clustering to subdivide research papers with respect to scientific schools. There is defined the quality metric of cluster solution. The developed methods were tested for e-libraries and for academic institutions.